Limited Liability Company's Status After Insolvency: Dissolution or Rehabilitation? - Doni Budiono; Maria Clarisa Talia (Pandecta Research Law Journal, 2023)
Bankruptcy and postponement of debt payment obligations are facilities given by law to encourage collective debt settlement for debtors that are experiencing financial distress and therefore on a status of bad credit. After the debt settlement process is over, the debtor according to Article 215 - 221 Indonesian Law Number 37 Year 2004 (“Indonesia Insolvency Law”) may request for financial rehabilitation. However, towards debtors whose form of legal entity is a limited liability company (“LLC”) it is regulated in Article 142 paragraph (1) letter e Indonesian Law Number 40 Year 2007 (“Indonesia LLC Law”) for such debtors to be dissolved after being condemned insolvent. These two variations of regulation allows room for conflict especially towards an LLC that is both capable and willing to continue their business after the removal of the insolvency status but is hindered by the Indonesia LLC Law. Therefore, this research is conducted in order to analyze the legal consequences of an LLC that–after being released from insolvent status–wishes to continue its business and has sufficient capability of doing so, based on both the Indonesia Insolvency Law and the Indonesia LLC Law. This research is normative research that uses statute approach and conceptual approach. The result of this research is that the dissolution regulation may be ruled out if the LLC has the ability to continue its business post-insolvency, under the condition that the LLC must plead for rehabilitation, having a written proof of payment satisfaction from the creditors.